University physics - Arfken, George B. (George Brown), 1922- (Academic Press, 1984)
University Physics provides an authoritative treatment of physics. This book discusses the linear motion with constant acceleration; addition and subtraction of vectors; uniform circular motion and simple harmonic motion; and electrostatic energy of a charged capacitor. The behavior of materials in a non-uniform magnetic field; application of Kirchhoff's junction rule; Lorentz transformations; and Bernoulli's equation are also deliberated. This text likewise covers the speed of electromagnetic waves; origins of quantum physics; neutron activation analysis; and interference of light. This publi.